Apoloniškoji apgaulė (kitoks Maironio „Pavasario“ perskaitymas) - Jurgutienė, Aušra (Literatūra, 2009)
In the article the problem of methodology of literary research is discussed. There is given the deconstruction of the phenomenological interpretation of the poem “The Spring” by Maironis, discussed its traditional understanding, suggested a new approach for reading the classics work and made the extend of criticism language. The basics theoretical differences between phenomenology and poststructuralism approaches in the literary criticism were talk over too.